Expert hydrogen perspectives for technological innovation: A Q-method study. (2nd March 2015) - Baxter, Jenifer; Hacking, Nick
Abstract There are currently a number of fundamental sustainability challenges which impact upon a variety of social, economic and environmental domains. One of these is energy supply where significant uncertainties exist in how best to tackle the multi-dimensional problems being raised in each of these areas. Because of this uncertainty, normative approaches to the development of low-carbon technological innovations will always contested. Q methodology, an established form of discourse analysis, was therefore undertaken in order to explore the competing visions and perspectives of experts working in the radical technological field of hydrogen production from waste. This is the first time that the perspectives of expert stakeholders involved in a technological innovation system (TIS) for hydrogen have been investigated using Q methodology. These contributors revealed limited awareness of each other. From this, we conclude that improvements need to be made to policies aimed at boosting the networks being used by the broad community of hydrogen-from-waste professionals. In particular, efforts should be centred on the skills required to manage the dissemination of communication regarding successful innovation.